Meta-Analisis Pengaruh Model Problem Based Learning terhadap Kemampuan Berpikir Kritis Siswa - Ananda Mahaputra Iskandar; Dinda Nurfadiah; Widia Iswari Yuli; Desnita Desnita (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2021)
This meta-analysis research was conducted with several objectives. First is analyzing that influence given by the problem-based learning model of students' critical thinking skills. Second is to analyze the magnitude of the influence exerted by the problem based learning model based on the level of education (SMA and SMP). The third is to review the magnitude of the influence of using the problem-based learning model based on the material being taught (Work and Energy, Fluid, Substance Pressure, Motion, Elasticity, Harmonic Vibration, Electric Current and Electrical Resistance, Temperature and Heat). The fourth examines the magnitude of the influence of the problem-based learning model based on grade levels (VII, VIII, X and XI). The method used in this research is meta-analysis, which is to analyze 20 articles from existing research. Obtained 4 effect size values from the research that has been done. For the effect size, the ability to think critically is 2.25 which is in the high category. Aspect effect size based on the level of education is 2.43 for SMA level. The effect size for the aspect based on the material is 2.99 for the fluid material and the effect size for the aspect based on the grade level is 3.33 at grade XI level.